Comprensión lectora en estudiantes de cuarto de primaria de La Perla Alta y Perla Baja del Callao - Díaz Ricalde, Luisa Margarita (2011)
The present investigation´s purpose is to determine and compare the reading comprenhension in students of fourth grade from La Perla Alta and La Perla Baja districts. A sample of 95 and 101 students was considered from each school respectively. The type of design used was random probabilistic, descriptive, comparative with ages between 9 and 12 years. The test used was extend of the reading comprehension for fourth grade ACL 4, which considers the following dimensions: literal, reorganizative, inferential and critical. The principal results were that it exists a difference in reading comprehension in students of La Perla Alta y La Perla Baja districts in literally and inferential aspects and there is no difference in reorganizative and critical aspects. As additional information there was not a significants differences in reading comprehension between males and females students.